Changing Patterns of Drug Abuse and Criminality Among Crack Cocaine Users in New York City: Criminal Histories and Criminal Justice System Processing, 1983-1984, 1986 - Fagan, Jeffrey ([Verlag nicht ermittelbar], 1992)
This data collection compares a sample of persons arrested for offenses related to crack cocaine with a sample arrested for offenses related to powdered cocaine. The collection is one of two parts of a study designed to examine the characteristics of crack users and sellers, the impact of large numbers of crack-related offenders on the criminal justice system, and their effects on drug treatment and community programs. Official arrest records and supplementary data bases are used to analyze the official arrest, conviction, and incarceration histories of powdered cocaine and crack defendants. Questions addressed by the collection include: (1) How are defendants charged with crack-related offenses different from defendants charged with offenses related to powdered cocaine? (2) Is there a difference between the ways the criminal justice system handles crack offenders and powdered cocaine offenders in pretrial detention, charges filed, case dispositions, and sentencing? (3) How do the criminal careers of crack offenders compare with the criminal careers of powdered cocaine offenders, especially in terms of total arrest rates, frequencies of nondrug crimes, and frequencies of violent crimes? (4) Is violence more strongly associated with crack dealing than with powdered cocaine dealing? and (5) How does the developmental history of powdered cocaine sales and possession compare with the history of crack sales and possession? Variables include demographic information such as gender, residence, and race, arrest, conviction, and incarceration histories, prior criminal record, community ties, and court outcomes of the arrests.